Evaluation of the right heart using cardiovascular magnetic resonance imaging in patients with cardiac devices. (1st October 2020) - Löbe, S.; Paetsch, I.; Hilbert, S.; Spampinato, R.; Oebel, S.; Richter, S.; Döring, M.; Sommer, P.; Bollmann, A.; Hindricks, G.; Jahnke, C.
Abstract: Background: Patients with cardiac implantable electronic devices (CIED) necessitate comprehensive cardiovascular magnetic resonance (CMR) examinations. The aim of this study was to provide data on CMR image quality and feasibility of functional assessment of the right heart in patients with CIED depending on the device type and imaging sequence used. Methods: 120 CIED carriers (Insertable cardiac monitoring system, n = 13; implantable loop-recorder, n = 22; pacemaker, n = 30; implantable cardioverter-defibrillator (ICD), n = 43; and cardiac resynchronization therapy defibrillator (CRT-D), n = 12) underwent clinically indicated CMR imaging using a 1.5 T. CMR protocols consisted of cine imaging and myocardial tissue characterization including T1-and T2-weighted blackblood imaging and late gadolinium enhancement (LGE) imaging. Image quality was evaluated with regard to device-related imaging artifacts per right-ventricular (RV) segment. Results: RV segmental evaluability was influenced by the device type and CMR imaging sequence: Cine steady-state-free-precision (SSFP) imaging was found to be non-diagnostic in patients with ICD/CRT-D and implantable loop recorders; a significant improvement of image quality was achieved when using cine turbo-field-echo (TFE) sequences with a further improvement on post-contrast TFE imaging. LGE scans were artifact-free in at least 91% of RV segments with best results in patients with a pacemaker or an insertable cardiac monitoring system. Conclusions: In patients with CIED, artifact-free CMR imaging of the right ventricle was performed in the majority of patients and resulted in highly reproducible evaluability of RV functional parameters. This finding is of particular importance for the diagnosis and follow-up of right-ventricular diseases. Highlights: Artifact-free right heart CMR imaging in CIED patients succeeded in the majority. CMR image quality resulted in highly reproducible evaluability of RV parameters. Excellent CMR image quality was achieved even with non-MR-conditional devices.